2002
DOI: 10.1016/s0378-5173(02)00297-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of naltrexone-loaded hydrolyzable crosslinked nanoparticles

Abstract: A hydrolyzable crosslinker (N,O-dimethacryloylhydroxylamine (MANHOMA)) was synthesized by a modified method and was characterized using 1 H-NMR, FTIR, and melting point determination. Naltrexone-loaded nanoparticles were prepared by copolymerization of poly(ethylene glycol)1000 monomethyl ether mono methacrylate (PEO-MA), methyl methacrylate (MMA) and N,O-dimethacryloylhydroxylamine (MANHOMA) in 0.4% poly(vinyl alcohol) aqueous solution. The nanoparticles were characterized by FTIR, particle size determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…The fractions were compared by TLC (silica gel using petroleum ether-EtOAc as solvent), and those giving similar coumarin spots were combined and further purified on preparative TLC to give Farnesiferol C (5.43 mg). The melting point, H-and C-NMR data of the obtained isolated farnesifeol C were confirmed according to previously published works [21,22,23].…”
Section: Preparation Of Extract and Chromatographysupporting
confidence: 53%
“…The fractions were compared by TLC (silica gel using petroleum ether-EtOAc as solvent), and those giving similar coumarin spots were combined and further purified on preparative TLC to give Farnesiferol C (5.43 mg). The melting point, H-and C-NMR data of the obtained isolated farnesifeol C were confirmed according to previously published works [21,22,23].…”
Section: Preparation Of Extract and Chromatographysupporting
confidence: 53%
“…Naltrexone was the first drug to receive FDA approval to treat alcohol dependence (4)(5)(6)(7). Because of the extensive first-pass metabolism in the liver, only 5-20 % of the oral dosage of this drug reaches the systemic circulation unchanged (4,8).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a controlled-release parenteral formulation of which a single injection may release the drug over a week, month, or even longer is especially desirable. Early trials have suggested that the sustained release of naltrexone may be appropriate for the management of either alcohol or opioid dependence (5,13,14). There are several systems for the subcutaneous implantation of naltrexone hydrochloride (9,(15)(16)(17), but this route of administration requires intricate technology, and it is too expensive (8).…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles are separated from the original liquid phase to eliminate the organic solvent(s) and the nonencapsulated drug. Preferably, the filtration is carried out at 25 C with an ultrafiltratio membrane.…”
mentioning
confidence: 99%
“…And, it is possible to conclude that the formation of hydrogel layer at 37 C might act as additional diffusion barrier for the drug release. 19,22,25 CONCLUSIONS Naltrexone was successfully encapsulated into the Poly(NIPAAm-AAm-VP) and its blend with PLGA. The yield of encapsulation of naltrexone in Poly(NIPAAm-AAm-VP) and PLGA (NIPAAm-AAm-VP) was 34-65%.…”
mentioning
confidence: 99%